The academic reception of Emil Staiger's concept in Bulgaria (Colloquia Comparativa Litterarum, 2025)
My goal is to present the reception of several writings by Emil Staiger in the Bulgarian academic environment. Also – to pose a more general question – do approaches to these writings imply credibility? The publications I discuss are by Rossitza Dimtshewa, Nikola Georgiew, Atanas Natew.
Keywords: Emil Staiger; reception in Bulgaria; reliability; Rossitza Dimcheva; Nikola Georgiev; Atanas Natev